Patterns of Cardiac Arrhythmia in Haemodialysis Patients (Anwer Khan Modern Medical College Journal, 2017)
Background: Cardiovascular disorders are one of the most serious problems in chronic haemodialysis patients. According to the records of last 15 years, 50% of these patients died from cardiovascular complications every year, without a marked reduction in the annual frequency of deaths. Cardiac arrhythmias are frequently associated with haemodialysis and have been reported to be seen in some series in up to 76% of patients.Materials & Methods: They appear to occur mostly after the first 3 hours of dialysis. In this study we have evaluated the arrhythmias that occured before and during dialysis to reduce the burden of morbidity and mortality of the patients. This is a cross sectional descriptive type of observational study on haemodialysis patients in Medical College for Women and Hospital (MCWH). Duration of study was 2 years, from July 2011 to June 2013.All the patients of end stage renal disease (ESRD) on maintenance haemodialysis (MHD) were included in the study. 81 patients were included to the study. One patient had permanent pacemaker and was excluded. Four patients had died during the study and four patients did not co-operated and left the study. Holter monitoring of a patient was unreadable because of artifact. Finally 71 patients were studied.Results: Out of 71 patients 38 were males and 33 were females with male to female ratio of 1.5:1. The mean age of the patient was 50.81 12.45 ( Range-22-75 ) year. Among 71 patients 19 had both DM and HTN and 42 patients had only HTN and 10 patients had other causes of chronic kidney disease (CKD).Premature atrial contraction(PAC) 27(40.30%) and Premature ventricular contraction(PVC) 40(59.70%)were the most common arrhythmia in dialysis patients before and during dialysis in our study. We found no significant effect of heamodialysis (HD) on cardiac arrhythmia. There was no correlation between arrhythmia and changes in Hb%, HbA1C, S. Albumin, S Creatinine, ions changes(Na+, K+, Ca++, Mg++)before and during haemodialysis (HD). QT intervals had no significant increase in dialysis patients. The prevalence of Atrial fibrillation (AF) rhythm was 5.63%.A high prevalence of cardiovascular disease is observed in end stage renal disease(ESRD) patients receiving dialysis therapy.Conclusion: The number of arrhythmias did not increase during dialysis in patients with no history of cardiac diseases, so the dialysis itself is not a leading risk factor for arrhythmias. But if a patient has history of arrhythmia, ischemia or left ventricular hypertrophy(LVH), he should be monitored during haemodialysis or undergo peritoneal dialysis in order to reduce the arrhythmia risk.Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 28-33